Uncertainty Encountered by the Humanities and Social Science Undergraduates in their Information Seeking Behaviour - Wijetunge, Pradeepa (Library Network, Eastern University, Sri Lanka, 2018)
This paper discusses the negative feelings of Humanities and Social Science undergraduates in their information seeking and using behavior, elicited during a series of Focus Group meetings. It is revealed that throughout the entire process of information seeking and using related to their academic assignments, the majority feels unhappy due to several factors which can be categorized as library-related, subject-related, processrelated and administration-related. However, it is asserted that further ethnographic research across the universities is needed to substantiate and generalize the findings. Nevertheless, the attention is drawn to the significant role that has to be played by the librarians in order to develop the confidence of undergraduates and support them to reach maturity in their information seeking behavior corresponding to their advancement in academic years.
Keywords: Undergraduates, Uncertainty, Information Seeking Behaviour